Authentic Materials in Teaching Speaking: A Study on Students’ Motivation and Fluency - Iim Khairunnisa; Faiz Fauzan Muhajir; Dewata Carolia Sarjono; Eka Dewi Fithrotunnisa (ELT (English Language Teaching Prima Journal), 2026)
This study investigates the impact of authentic materials on students’ speaking motivation and fluency in an English language education program. Using a qualitative case study design, data were collected from 10 purposively selected students through questionnaires, fluency rubrics, and classroom observations over eight weeks. Findings reveal that authentic materials significantly enhance learners’ motivation, particularly in effort and persistence (96.67%) and relevance and usefulness (96%), while also fostering enjoyment (93.08%). Although confidence and participation scored slightly lower (83.33%), results remain positive. In terms of fluency, students demonstrated strong performance in pronunciation and intonation (97%) and vocabulary and expression (97%), with confidence (89.33%) and flow (86%) showing room for further improvement. Overall, authentic materials provide meaningful, real-life language exposure that strengthens motivation, builds confidence, and improves fluency, highlighting their effectiveness in speaking instruction for university-level learners.